Nivel de informação de mulheres sobre câncer de colo do útero - Leite, Maria Fernanda (2010)
In Brazil, the incidence of cervical cancer is highly related to lack of information and therefore it is important to assess the knowledge of the female population on the subject, and from that, develop strategies to reduce the occurrences. For this reason this study was to identify with the level of women's information in a neighborhood of Bauru, São Paulo, Brazil on what is cervical cancer, its causes and ways of prevention. We conducted a descriptive transversal study with 450 women aged 25 to 59 years, through a structured interview subjects' own homes. For the analysis of data was descriptive statistics. The data revealed that 305 (67.77% could not properly define what is the disease and 141 (31.33%) women incorrectly set, with the latter, 87 (19.33%) believe that cervical cancer the uterus is a wound; 309 (68.66%) no answer about what can cause a woman to develop cervical cancer, 58.0% reported that the primary form of prevention is a Pap smear and 25 11% no answer. One can conclude that it is necessary for practice of health education are implemented and enforced in order to broaden the knowledge on the subject by the population.